2012
DOI: 10.3329/bjmm.v6i2.19370
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of dermatophyte in Bangabandhu Sheikh Mujib Medical University

Abstract: Dermatophytes are by far the most significant fungi because of their widespread involvement of population at large and their prevalence all over the world. This is an attempt to observe the spectrum of dermatophytes among the clinically suspected cases of dermatophytosis attending the outpatient department of Dermatology and Venereology, Bangabandhu Sheik Mujib Medical University, Dhaka. Three hundred and twenty clinically suspected cases of dermatophytosis were subjected to mycological studies. One hundred an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…[ 10 ] Various studies have reported different gender prevalence of dermatophytosis. [ 11 12 13 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Various studies have reported different gender prevalence of dermatophytosis. [ 11 12 13 14 15 16 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…They are flattened, elliptical with 0.5 mm in diameter and colour is creamy-white but change to red before hatching (Alam et al, 2006). The egg takes incubation period of 3-5 days in summer and 7-8 days in winter and hatche into dark white larvae (Rahman, 2006).…”
Section: Life Cyclementioning
confidence: 99%
“…The larval period lasts 12 -15 days during summer and 14 -22 days during winter season (Rahman et al, 2006). Larvae pass through at least five instars (Atwal, 1976) and there are reports of the existence of six larval instars (Baang and Corey, 1991;FAO, 2003).…”
Section: Larvamentioning
confidence: 99%
See 1 more Smart Citation
“…In Bangladesh hot and humid climate, overcrowded population, poverty and malnutrition make dermatophytosis a very common superficial infection. 3 Study conducted worldwide showed that antifungal resistance of dermatophytosis very common particularly against azoles drug group due to irrational and overuses of them.…”
Section: Introductionmentioning
confidence: 99%